2021
DOI: 10.3390/vetsci8020022
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in Cats with Acute Onset of Severe Thoracolumbar Spinal Cord Injury Following Physical Rehabilitation

Abstract: The literature is lacking data concerning the prognosis in cats suffering from naturally occurring acute onset of thoracolumbar (TL) spinal cord injury that are undergoing rehabilitation therapy. Therefore, we investigated the effect of physical rehabilitation in cats suffering from naturally occurring TL spinal cord injury. The medical records of 36 cats with acute onset of TL spinal cord injury that were selected for rehabilitation treatment were reviewed. Twenty-nine cats underwent an intensive physical reh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…This study did not show a significant impact of rehabilitation on the outcome. However, several studies revealed that rehabilitation is a crucial factor in improving better outcomes of spinal injuries (Gallucci et al, 2020;Gallucci et al, 2021). Therefore, the rehabilitation method, duration, and frequency of rehabilitation should be studied more specifically in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This study did not show a significant impact of rehabilitation on the outcome. However, several studies revealed that rehabilitation is a crucial factor in improving better outcomes of spinal injuries (Gallucci et al, 2020;Gallucci et al, 2021). Therefore, the rehabilitation method, duration, and frequency of rehabilitation should be studied more specifically in future studies.…”
Section: Discussionmentioning
confidence: 99%